2010
DOI: 10.1007/s12028-010-9461-z
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and Clinical Effects of the Supplementation of a Functional Mixture of Amino Acids in Cerebral Hemorrhage

Abstract: Supplementation with specific amino acids in critically ill patients may modulate metabolic response and improve clinical outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…The decrease in blood white cell count was greater in treated patients (–18%) than in the placebo recipients (–4.4%). The improvement in lymphocyte counts found in this study is in line with that observed in a recent investigation carried out in individuals in an ICU treated with the same formula, at the same dose as that used in the current study 45 …”
Section: Methodssupporting
confidence: 92%
“…The decrease in blood white cell count was greater in treated patients (–18%) than in the placebo recipients (–4.4%). The improvement in lymphocyte counts found in this study is in line with that observed in a recent investigation carried out in individuals in an ICU treated with the same formula, at the same dose as that used in the current study 45 …”
Section: Methodssupporting
confidence: 92%
“…The CATHON formulation does not contain arginine and yet proved to be extremely efficient in promoting improved physical activity both in diabetic patients with chronic heart failure [41] and patients with chronic obstructive pulmonary disease, where an impressive improvement in blood PO 2 was documented [42]. Interestingly, a ‘side effect’ of CATHON administration is improved insulin sensitivity, as shown by long-term supplementation studies in the elderly [43] and, more recently, in extremely severe intensive care unit patients [44]. CATHON enhances insulin action thanks to enhanced mTOR activity [45], with important clinical implications [22].…”
Section: Interactions Between Inos and Enos And Control Of Enos Exprementioning
confidence: 99%
“…In patients with chronic kidney disease, EAA supplementation proved to be more effective than ovalbumin‐similar formulations in promoting synthesis of visceral proteins without altering urea production . Similar findings were observed in diabetic patients affected by chronic heart failure , , and in intensive care unit patients after neurosurgery . Therefore, we should always ask ourselves, if increases in urea excretion are a sign of an ameliorated nitrogen balance, or if such increases simply mirror an inadequate EAA availability as part of excessive non‐essential AA supply, i.e., the failure of supply to match requirements and needs.…”
Section: The Knot Of Calculating Nitrogen Needs By Urea Synthesismentioning
confidence: 71%